VD_FINDINFO Décision / 2018 / 922 vom 5. Dezember 2018 - VD Tribunal cantonal (2018)
CLASSEMENT DE LA PROCÉDURE, DROIT D'ÊTRE ENTENDU, ESCROQUERIE, GESTION DÉLOYALE | 146 CP, 158 CP, 29 Cst., 319 CPP (CH)